Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

y = -x + 2 –6x + 2y = 8​

Sagot :

Answer:

rewrite the whole expression;

X+Y =2

-6x + 2y = 8

divide the 2nd expression by 2 on both sides we get

-3x + y = 4

substract the 1st expression from the newly found 2nd expression

-3x-x + y-y = 8-2

-4x = 6; x= 3/2

y = 2-(3/2) = 1/2

x= 3/2 , y= 1/2